ダイ8ジ ナンキョク チイキ カンソク エットウタイ キョクコウ ブモン ホウコク (1967-1968) - 神沼, 克伊; カミヌマ, カツタダ; 平沢, 威男; ヒラサワ, タケオ; KAMINUMA, Katsutada; HIRASAWA, Takeo (国立極地研究所, 1969)
P(論文) The auroral observations carried out by the 8th wintering party of the Japanese Antarctic Research Expedition, 1967-68, included 1 All-sky camera 2 Visual and photographic observations of aurora 3 Observation of auroral pulsations 4 Auroral photometry along the geomagnetic meridian 5 Observation of the auroral radio noise A description of each observation and obtained results are briefly given 1 Auroral pulsations A special photometer was designed for investigating the detailed characteristics of auroral pulsations and their relationships with geomagnetic pulsations The photometer (Fig 1) consists of a single telescope equipped with a band-pass filter (4278 A) The field of view is 5° The amplified anode current of the RCA lp21 photomultipliers is fed to three electrical band-pass filters (f_1, 001-01 Hz, f_2, 01-2 Hz, f_3, 2-30 Hz), and recorded by a slow running tape-recorder The outputs of the band-pass filters are separately registered on multi-channel pen recorders together with the signals of the geomagnetic pulsations By means of this photometric system, data of more than 300 clear night hours were recorded (Fig 3) Figs 4-8 illustlate the various types of auroral luminosity fluctuations together with the geomagnetic field fluctuations Auroral pulsations observed at Syowa Station can be classified into the following five types. A. Irregular fluctuations with large amplitudes (a few tens of KR) observed mostly at the onset of an auroral substorm (Fig 4) B Pulse-like auroral pulsations with a period of about 20-40 seconds, the amplitudes of which are sometimes greater than 10 KR Pulsations of this type are frequently observed in the early morning hours of magnetic disturbed days (Fig 5). C Long-lived auroral pulsations with a sinusoidal waveform. Their periods and amplitudes are about 10 seconds and a few KR, respectively. This type is dominant in the morning hours (Fig. 6). D. Rapid fluctuations of auroral luminosity with a period of about 2-0.5 seconds (Fig 7, A and B). E. Extremely rapid ...